Die Studentenbewegung 1968 im Spiegel d e r deutschen Presse. Ein Überblick über die Schlagzeilen zur Anti-Springer-Kampagne im April 1968 - Szczebrak, Jacek (Glottodidactica, 2005)
This article describes the attitudes of German press to the events of the student protest in West Berlin and West Germany in 1968. A number of headlines from five major German newspapers and magazines (from Das Bild to Neues Deutschland) have been chosen to illustrate how the same facts were differently interpreted by left-wing and right-wing journalists. The language of political propaganda is in the author"s focus of attention although the first part of the article also covers some historical aspects of the student revolt. Since the media played an active role in the revolt on both sides of the social conflict, this short analysis of the German press might be of interest to linguists and historians alike. Among the analyzed linguistic aspects of the headlines are the following: the degree of neutrality or objectivity vs. emotional bias, the use of quotations, irony, colloquialisms as well as the perspective and the content of the headlines as speech acts. On this basis the author tries to define the position of the five newspapers and magazines in the political debate about the events of 1968 which continues to this day.